Health Promotion Strategies to Strengthen Anti-Smoking Policies: From Picture Warnings to Smoke-Free Area - Dewi, Riskha Dora Candra; Al Mujib, Ihwan Huda (P3M Politeknik Negeri Jember, 2025)
One of the primary factors contributing to Indonesia's rising non-communicable disease burden is cigarette smoking. Government anti-smoking policies include the establishment of smoke-free areas (KTR), the ban on cigarette advertising, promotion, and sponsorship, and the use of pictorial health warnings on cigarette packaging in an effort to lower the number of smokers and shield the public from the risks associated with cigarette smoke exposure. However, effective health promotion measures that are implemented widely, methodically, and on target are crucial to the success of these initiatives. The objective of this paper is to determine the way health promotion strategies promote Indonesia's anti-smoking regulations. This article employs a literature review method to investigate various health promotion media, including visual advertising, social media, and community participation in raising awareness about the risks of cigarettes and the significance of a smoke-free environment. The findings of the study indicate that integrated and evidence-based promotional techniques can raise public knowledge of the dangers of smoking and enhance acceptance of laws such as KTR and cigarette advertising bans. Furthermore, cross-sector cooperation, which includes educational institutions, civil society organizations, and the media, is critical to the achievement of developing a healthy culture and environment that promotes a smoke-free lifestyle. To broaden and sustain the impact of promotion, risk communication policies must be strengthened, and health message delivery must be innovative. Effective health promotion initiatives serve as a link between policy and changes in community behavior.